Acute Pancreatitis as Initial Presentation of Cocaine-Induced Vasculitis: A Case Report - Ogunbameru, Ayorinde; Jandali, Mohammed; Issa, Amer; Quwatli, Waleed; Woodlock, Timothy; Choudhry, Wajid (JOP. Journal of the Pancreas, 2015)
Context Levamisole-contaminated cocaine is an increasingly reported cause of vasculitis and immunologic abnormalities in cocaine abusers. The systemic effects of vasculitis are commonly seen in the dermatologic, hematologic and renal systems but rarely the gastrointestinal system. Case report We present an atypical case of cocaine-induced vasculitis presenting initially as an acute pancreatitis and then rapidly progressing to involve multi-organ systems over the next couple of weeks. Conclusion Internists should recognize that acute pancreatitis can present as an atypical and rare initial systemic manifestation of cocaine-induced vasculitis. Image: Segmental glomerular necrsosis.